Peroxisome proliferator-activated receptors and retinoic acid receptors differentially control the interactions of retinoid X receptor heterodimers with ligands, coactivators, and corepressors. - DiRenzo, J (1997)
As the obligate member of most nuclear receptor heterodimers, retinoid X receptors (RXRs) can potentially perform two functions: cooperative binding to hormone response elements and coordinate regulation of target genes by RXR ligands. In this paper we describe allosteric interactions between RXR and two heterodimeric partners, retinoic acid receptors (RARs) and peroxisome proliferator-activated receptors (PPARs); RARs and PPARs prevent and permit activation by RXR-specific ligands, respectively. By competing for dimerization with RXR on response elements consisting of direct-repeat half-sites spaced by 1 bp (DR1 elements), the relative abundance of RAR and PPAR determines whether the RXR signaling pathway will be functional. In contrast to RAR, which prevents the binding of RXR ligands and recruits the nuclear receptor corepressor N-CoR, PPAR permits the binding of SRC-1 in response to both RXR and PPAR ligands. Overexpression of SRC-1 markedly potentiates ligand-dependent transcription by PPARgamma, suggesting that SRC-1 serves as a coactivator in vivo. Remarkably, the ability of RAR to both block the binding of ligands to RXR and interact with corepressors requires the CoR box, a structural motif residing in the N-terminal region of the RAR ligand binding domain. Mutations in the CoR box convert RAR from a nonpermissive to a permissive partner of RXR signaling on DR1 elements. We suggest that the differential recruitment of coactivators and corepressors by RAR-RXR and PPAR-RXR heterodimers provides the basis for a transcriptional switch that may be important in controlling complex programs of gene expression, such as adipocyte differentiation.